The Position and Legal Protection of Advocates in Carrying Out Professional Duties at the Investigation Level - Muhammad Fithrah Fanani; Heni Ibtiani; Daud Badar Isroil; Musleh Harry (Universitas Islam Negeri Sumatera Utara, 2026)
Advocates hold a strategic position in the criminal justice system as law enforcers who function to maintain a balance between state authority and the protection of suspects' rights, particularly during the investigation stage. This study aims to analyze the position of advocates and the effectiveness of their legal protection in investigative practice. This study uses normative legal methods with a statutory and conceptual approach. The results of the study indicate that normatively advocates have received guaranteed legal protection through the right to immunity and confidentiality of advocate-client relationships as regulated in the Advocates Law and Constitutional Court Decision Number 26/PUU-XI/2013. However, in its implementation, this protection has not been effective due to unclear boundaries of good faith, the dominance of investigators' authority, and a legal culture that has not placed advocates as equal partners in the criminal justice system. This study concludes that the gap between norms and practices has resulted in a weakening of the advocate's function in ensuring due process of law, equality before the law, and access to justice. Therefore, it is necessary to strengthen the consistency of law enforcement and reconstruct the understanding of law enforcement officials regarding the position of advocates in the criminal justice system.